ANALISIS FITUR CITRA PRASASTI LOGAM MENGGUNAKAN METODE GRAY LEVEL RUN LENGTH MATRIKS(GLRLM)) - Setiawan, I Kadek Dedi; Rasmana, Susijanto Tri; Wibowo, Madha Christian (Journal of Control and Network Systems, 2015)
East java is a center of Majapahit kingdom, who has many inscription. One of them is Adan-adan inscription. It was kept in Mpu Tantular museum. The prehistorical of the inscription Â was filled with Javanese ancient writing. It finded on few centimeters under land surfaces, because of it many inscription had finded realized broken like rusty on the copper plate line and many of letter scratch then in the others part was lid by rusty, so make the information deliver of the inscription less. The inscription realize texture feature changing on the scratch from Adan-adan plate.This research purpose to classified scratch fiture and inscription plate based on GLRLM feature extract used SVM method in order to differentiate kind of inscription between scratch and brown patina plate and green patina. For decide accuration level in the scratch and brown patina plate and green. It used for SVM classified based on GLRLM feature extract.From GLRLM extract feature trial obtain feature value from the scratch and brown and green patina plate. When feature value from the scratch and brown and green patina plate get different feature, so the scratch and plate can classified. SVM classification based on GLRLM feature extract from scratch get maximum accuration level reached 73,33% and inscription plate get maximum accuration level reached 79,17%.